Jamaluddin Al-Afghani's Thoughts on Islamic Education - Taufik Marwina Hakim (Penerbit Hellow Pustaka, 2024)
The thought of Islamic education in the perspective of Jamaluddin al-Afghani can be described as a progressive and holistic vision that places education as the main instrument to overcome the challenges of the times, improve the sustainability of Muslims, and develop an intelligent and ethical society. The thinking of Islamic education from the perspective of Jamaluddin al-Afghani has a number of key objectives that reflect his determination to enhance the progress of Muslims. It involves liberating Muslims from the shackles of colonialism, overcoming setbacks and backwardness, developing superior individuals, integrating modern science, forming critical thinking skills, renewal in thought and action, creating unity among Muslims, as well as awakening the spirit of development.